Preparation of Imidazole Derivatives via Bisfunctionalization of Alkynes Catalyzed by Ruthenium Carbonyl - Ruan, Yi-tong; Chen, Yue-peng; Gu, Ling-hui; Luo, Yang; Yang, Ze; He, Ling (Synthesis, 2019)
A one-step, oxidative bisfunctionalization of alkynes to generate cis-enediol diacetates catalyzed by ruthenium carbonyl (triruthenium dodecacarbonyl) is presented. The reaction was performed using the alkyne, (diacetoxyiodo)benzene, Ru3(CO)12 as the catalyst, and toluene as the solvent at 100 °C to give the cis-enediol diacetates in up to 82% yields. This method overcomes the shortcomings of existing methods, such as tedious reaction steps, substrate limitations, and the use of toxic reagents. Furthermore, the reaction of module cis-enediol diacetates with ammonium carbonate [(NH4)2CO3] in an alcohol solvent gave imidazole derivatives in 37–84% yields, thus providing a simple and mild new method for the synthesis of imidazole compounds.
Keywords: imidazoles; bisfunctionalization; alkyne; cis-enediol diacetate; ruthenium carbonyl